“Dari Mata Turun ke Hati”: Penggunaan Eyelash Extensions di Kalangan Siswi Sekolah Menengah - Valensia, Putri Aurelia (Universitas Muslim Maros, 2023)
Being attractive and beautiful has its own charm which will certainly increase self-confidence. For this reason, women try to improve their appearance, one of which is by doing facial treatment to make them look more attractive. One of the current trends is eyelash extensions which are widely used by women. This article deals with this. This research used a qualitative approach, and it was conducted in Makassar, involving ten female Junior and Senior High School students in Makassar. They are between 14 and 18 years old. Data collection was carried out througuh in-depth interview and observation. Beauty is every woman's dream regardless of age. There are various ways to look beautiful. Eyes are the main aspect of beauty because as a saying state: